Perkembangan Moral Anak Dalam Perspektif Pendidikan: (Kajian Teori Lawrence Kohlberg) - Hanafiah, Muktar (Yayasan Madinah Al-Aziziyah, 2024)
The moral development of children is a crucial aspect of education that plays a role in shaping their character and behavior. Lawrence Kohlberg's theory of moral development offers a framework that can be used to understand how children develop morally through certain stages. This article aims to examine children's moral development from an educational perspective by referring to Lawrence Kohlberg's theory. This study is expected to provide a deeper understanding of the importance of moral education and how Kohlberg's theory can be applied in the context of children's education. This research employs a literature review method, involving the identification, selection, collection, analysis, and synthesis of data from various relevant literatures. Data were obtained from books, scientific journals, articles, and other documents related to Lawrence Kohlberg's theory of moral development and its application in education. The results of the study show that Kohlberg's theory of moral development can be applied in children's education to help parents and educators understand the stages of children's moral development. A critical evaluation of this theory also reveals its strengths and weaknesses and its relevance in the current educational context. The conclusion of this study emphasizes the importance of applying moral principles in education to help children develop into individuals with strong morality and social responsibility.